2007
DOI: 10.1007/bf02931100
|View full text |Cite
|
Sign up to set email alerts
|

Rice bran lipase catalyzed esterification of palm oil fatty acid distillate and glycerol in organic solvent

Abstract: Rice bran lipase (RBL) was delipidated to enhance its stability in organic solvent and its esterification activity at elevated temperature. The esterification activity of delipidated RBL increased as temperature was increased from 45 to 65°C. The esterification activity of delipidated RBL at 65°C was about 14 times greater than that of the non-delipidated RBL. As temperature was further increased to 75°C, the non-delipidated RBL lost all esterification activity, whereas the delipidated RBL retained approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Evaporation of water under a stream of nitrogen gas (0.7 l min −1 ) was also reported to be capable of improving the DAG production yield as the presence of water favor hydrolytic reactions instead of synthetic reactions (Rosu et al 1999). Previous literature studies also indicated that the use of molecular sieves and silica as absorbent encouraged DAG synthesis even though the mentioned method is not practical in an industrial scale owing to the separation difficulties and increased overall manufacturing cost (Chong et al 2007;Kwon et al 1995;Lo et al 2004). …”
Section: Enzymatic Esterificationmentioning
confidence: 92%
“…Evaporation of water under a stream of nitrogen gas (0.7 l min −1 ) was also reported to be capable of improving the DAG production yield as the presence of water favor hydrolytic reactions instead of synthetic reactions (Rosu et al 1999). Previous literature studies also indicated that the use of molecular sieves and silica as absorbent encouraged DAG synthesis even though the mentioned method is not practical in an industrial scale owing to the separation difficulties and increased overall manufacturing cost (Chong et al 2007;Kwon et al 1995;Lo et al 2004). …”
Section: Enzymatic Esterificationmentioning
confidence: 92%
“…Rice bran contains lots of proteins, minerals, amino acids [1], lipase [2], and various antioxidant compounds, such as polyphenols [3], ferulic acids [3], γ-oryzanols [4], tocopherols, and tocotrienols [5]. Due to the antioxidant ability inhibiting the production of reactive oxygen species, rice bran has recently obtained much attention as a natural source of health food related to diabetes [6], atherosclerosis [7], and cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding cost reduction, Choi et al [42] showed that it might be possible to perform enzymatic esterification without the addition of enzymes. In that study, a FAME content of 87% could be obtained after 12 days via an in situ lipase-catalyzed reaction with only the addition of methanol [43]. Rice bran is known to contain several types of lipases (phospholipases, glycolipases, esterases), which might improve the economic sustainability of RBO pretreatment aiming at bioenergy production [43].…”
Section: Heterogenous Enzymatic Esterification Pretreatmentmentioning
confidence: 97%